Thalidomide induced impotence in male hematology patients: a common but ignored complication? - Philip T. Murphy; John Rory O’Donnell (Haematologica, 2007)
Thalidomide has become an important agent in the treatment of myeloma. However, thalidomide induced erectile dysfunction is a serious complication which has received very little attention. In our hematology department, 6 out of 11 male patients developed erectile dysfunction (grade 3 in 5/6) within 4 weeks of starting thalidomide. Our results suggest that thalidomide induced impotence is a common complication in male hematology patients.